Picking Cocoa, Trinidad - (:unkn) unknown (Wilsons Limited, 2010)
A picture of a group of labourers carrying baskets full of cocoa pods from the fields while another group work on breaking the pods to extract the beans.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; 1913; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Headgear--Trinidad and Tobago; Exports--Trinidad and Tobago; Harvesting--Trinidad and Tobago